1991
DOI: 10.1002/syn.890080303
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of aberrant serotonin‐immunoreactive fibers in the caudate putamen complex of the aged rat

Abstract: Degeneration of neurons in the central nervous system is associated with morphological changes. Previous observations made at the light microscopical level indicated degeneration of serotonin-immunoreactive (IR) fibers in the aged rat brain. In this study, a comparison at the ultrastructural level was made between serotonin-IR normal thin and aberrant swollen varicose fibers in the caudate-putamen complex of the aged rat. Ultrastructural features such as the size and content of the thin varicose fibers resembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These features become gradually more pronounced with age. Using electron microscopy, Van Luijtelaar et al (1992b) demonstrated the presence of distorted mitochondria and vacuolated membranes in the serotoninergic fibers of the normal aged rat. They considered these changes to reflect degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…These features become gradually more pronounced with age. Using electron microscopy, Van Luijtelaar et al (1992b) demonstrated the presence of distorted mitochondria and vacuolated membranes in the serotoninergic fibers of the normal aged rat. They considered these changes to reflect degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although 5-HT axon terminals (varicosities) in normal adult rat neostriatum do not often make synaptic membrane specializations (Soghomonian et a!., 1989;Van Luijtelaar et a!., 1991), the frequency of junctional terminals found in the 5-HT-hyperinnervated neostriatum does not change ('-~10%),indicating a greater absolute number of synaptic 5-HT varicosities (Descarries et a!., 1992). The proportion of the various cellular constituents in the immediate microenvironment of these 5-HT terminals also remains unchanged, furthering the view that these varicosities are mostly distributed randomly in relation to eventual cellular targets.…”
Section: Neonatal 6-ohda and 5-ht Neuronsmentioning
confidence: 99%